Bacterial diversity in longan orchard alluvial soil is influenced by cultivation time and soil properties - Nghia, Nguyen Khoi; Dalma, Kovacs Emoke; Haydee, Kovacs Melinda; Xa, Le Thi; Morton, Lois Wright; Tecimen, Hüseyin Barış; Robatjazi, Javad; Sekar, Jegan; Lasar, Hendra Gonsalve W.; Nguyen, Trung Thanh; Phuong, Nguyen Minh; Thy, Chau Thi Anh; et al. (Frontiers in Soil Science, 2025)
IntroductionLongan is a perennial crop and profitable export fruit well-suited to the Mekong Delta's climate and soils. Although soil deterioration in longan orchards has been studied, little research has addressed soil bacterial communities and their role in soil health. This study investigated the structure of soil bacterial communities and their associations with soil physicochemical properties in longan orchards.MethodsSoil samples were collected from longan orchards cultivated for 15 (N15), 20 (N20) and 30 years (N30) in Vinh Long Province, Vietnam. High-throughput sequencing of 16S rRNA amplicons was employed to assess bacterial diversity and community composition, followed by correlation analyses with soil properties.Results and DiscussionThe dominant bacterial phyla identified across sites included Acidobacteria, Proteobacteria, Chloroflexi, Actinobacteria, and Bacteriodota. Bacterial abundance in these soils was positively correlated with sand, pH, NO3- and phosphate solubilizing microorganisms, and negatively correlated with moisture, silt, clay, NH4+, exchangeable potassium and available manganese. Longan orchard soils from all three time periods (N15, N20, N30) had more microbial species in common, than in unique ways. However, time under cultivation was an important factor, with species diversity decreasing with age. The youngest orchards (N15) exhibited the highest number of soil bacterial diversity, followed by decreasing diversity as the orchards aged (N20) and lowest at 30 years (N30). Soil properties exhibited complex and interlinked relationships with soil bacterial phyla. Overall, long-term cultivation of longan orchard soil negatively impacted microbial diversity, potentially altering key properties of soil, hence underscoring the necessity for sustainable soil management to preserve soil health and production.